CircularSeas - Costa, Ana Maria Matias da (2021)
In recent years the problem of pollution has been increasingly debated, and one of the main issues discussed is related to the degradation of the oceans as a consequence of human activities. Polymeric materials are one of the main elements identified both on the coast and in the ocean itself, which causes several consequent adversities, both for human life and for the natural world. In order to analyze the possibility of reusing or reprocessing material usually considered waste, it is important to determine the type of properties that have been altered and what effect it would have on its use as a new raw material. Due to the limited amount of literature available on this subject, a large amount of polymeric material was collected from Peniche and Vieira beaches, Leiria, Portugal. As most identifiable objects were octopus traps and fishing nets, and knowing that this type of product is usually made of high-density polyethylene and polyamide, respectively, these were the materials chosen for analysis. The high density polyethylene was analysed both before and after processing, while on the case of the polyamide, only the processed material was analysed. Tensile, Dynamic Mechanical Analysis and hardness tests were performed after the necessary preparation. Comparing the values obtained in each case with the respective measurement of the virgin material, it was possible to observe that some properties, such as Young’s modulus, tension and tensile strength decreased considerably. Hardness was also affected, although it was less notorious. Seawater absorption tests were also carried out on virgin high density polyethylene in order to determine the amount of time the waste was under the influence of environmental degradation by comparing its density values over time with the density of waste material. However it was not possible to draw concrete conclusions since, in the case of density, it can easily vary depending on the type of conditions to which the material was subjected, which are unknown; on the other hand, the Dynamic Mechanical Analysis tests, used in the determination of the glass transition temperature, were inconclusive regarding high-density polyethylene since the value of this characteristic in the virgin material is lower than zero and, as the initial temperature used in the tests was the ambient temperature, it was not possible to determine the desired result, while this characteristic on the nylon waste decreased due to the material’s deterioration. After this project was carried out it was concluded that it is very important to correctly characterize this type of materials, not only at the mechanical level, but regarding other engineering fields, for example, at chemical level. Although some advantageous characteristics of virgin materials are lost, waste is still usable in different forms for new purposes, and can be treated as a new source of raw material.